Finite Element Analysis of Slope Stability of Fushun West Open-Pit Mine - Wang, Tong; Yuan, Lizhi; Bi, Mingli (Tehnički vjesnik, 2024)
Slope stability analysis is the earliest subject that classical soil mechanics tried to solve but has not yet been satisfactorily solved. Various stability analysis methods are roughly equivalent at home and abroad, while the current numerical analysis methods can generally only obtain slope stress, displacement, and plastic zone cannot obtain slope dangerous sliding surfaces and corresponding safety factor. With the development of computer technology, especially the development of nonlinear elastoplastic finite element calculation technology for geotechnical materials, the finite element strength reduction method has attracted attention in recent years. In this paper, the finite element strength reduction method is used to search for the dangerous sliding surface of the slope to obtain the corresponding stability safety factor, and the slope of Fushun West Open-Pit Mine in China is used as an example to analyze the calculation.